Geopolymer cement slurries with enhanced mechanical and physical properties for oilwell cementing - Ridha, S. (Institution of Engineering and Technology, 2014)
Cement integrity and durability in the wells is a major concern for oil industries in securing long term production especially after Macondo disaster. Recent studies show that there are several problems associated with the use of Portland cement such as permeability and strength degradation of well cement, susceptibility to chemical reactions, poor durability and leakage. In achieving these goals, the industries nowadays are seeking for cement systems that meet the technical requirements and at the same time can contribute to reduce greenhouse gas footprints. This paper evaluate the proposed geopolymer cement performance both in mechanical and physical properties under wellbore condition. Low calcium fly ash and silica fume were used as the main substitute materials varying in terms of mix proportion. The results of experimental investigations on geopolymer cement exhibit better properties compared to conventional cement. Superior performances of the new cement system are consistent up to 5 days of hydrations.